Connecting East Asia : (Asian Development Bank, 2005)
This study is about East Asia, and it¡¦s about infrastructure. It¡¦s about poverty and growth, and it¡¦s about transport, water, sanitation, power, and telecommunications ¡V both the infrastructure, and the infrastructure services. Infrastructure is only one part of the development challenge, but its impacts are among the most important. Connecting East Asia looks at the role that infrastructure has played in supporting East Asia¡¦s growth and looks ahead at what the challenges are for the future, and how to approach them